(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this study, the use of Carbon Fiber Reinforced Polymer (CFRP) laminates is investigated to strengthen old bridge girders. These girders weaken over time due to wear and environmental effects. CFRP offers a lightweight, strong reinforcement solution. The research investigates various bonding methods and laminate arrangements, testing the mechanical performance post-retrofitting effects. The results highlight the practical benefits of using CFRP, such as its ability to enhance stiffness and load capacity. Moreover, it is a cost-effective choice that minimizes traffic disruptions for older bridge systems.